Coronavirus Environment vs Socio-Economic and Demographic Problems Followed: A Sociological Appraisal - Mohammad Taghi Sheykhi (SIASAT, 2020)
The paper searches the cause and effect impacts of the newly-found Coronavirus. The word "Corona" is currently used by all the people (7.7 billion) over the age of at least 3. The unprecedented disease is reflecting a large number of effects infecting and killing many people of the rich and the poor. The new phenomenon is continuing rapidly. It brings about recessions and closures in many businesses, and laying off many employees and workers, and that has created income and security problems for the families. The new environment has imprisoned families inside homes disrupting them from the normal and regular interactions. Such people are getting frustrated indoors. The people confined at home are usually exposed and vulnerable to psychological disorders. Almost all those at school age, are banned to attend schools and higher educational institutions at all levels. So, the educational institution is also losing a lot. The new phenomenon needs sociological appraisal from various viewpoints. What is currently happening, will create problems in post-Corona age. One of the problems that will demographically impact the world nations is "migration". Many people of the poor countries will move to more developed countries where they hope to earn their living. So, social demographers need to mind the future scenario. Poor economies will not easily be able to rehabilitate and reconstruct themselves. That is why a large migration wave will be quite likely to occur. Similarly, many countries will face increasing child labor and street children because of shortage of employment for the adults. The method of research used in the present research is of qualitative type--collecting the data through library resources and other media. Findings prove that everybody is exposed to being affected, infected and killed through the Coronavirus.